2015
DOI: 10.1007/978-3-319-20267-9_32
|View full text |Cite
|
Sign up to set email alerts
|

Personality Correlates for Digital Concert Program Notes

Abstract: Abstract. In classical music concerts, the concert program notes are distributed to the audience in order to provide background information on the composer, piece and performer. So far, these have been printed documents composed mostly of text. With some delay, mobile devices are making their way also in the world of classical concerts, hence offering additional options for digital program notes comprising not only text but also images, video and audio. Furthermore, these digital program notes can be personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Table 1 shows the general dimensions with the corresponding primary factors. Table 1 The five-factor model adapted from McCrae and John [69] There is a growing amount of psychological literature investigating the relationship between personality traits and music consumption (e.g., [32,38,39,76,78,79,94]). For example, music preferences were found to be correlated with personality traits.…”
Section: Personalitymentioning
confidence: 99%
“…Table 1 shows the general dimensions with the corresponding primary factors. Table 1 The five-factor model adapted from McCrae and John [69] There is a growing amount of psychological literature investigating the relationship between personality traits and music consumption (e.g., [32,38,39,76,78,79,94]). For example, music preferences were found to be correlated with personality traits.…”
Section: Personalitymentioning
confidence: 99%
“…Personality has shown to be an enduring factor that can be related to a person's taste, preference, and interest (e.g., [9,26,28]). For example, Rawlings and Ciancarelli found relationships between personality traits and music genre preferences [26], while Tkalcic et al found relationships between personality and classical music [28]. These relationships indicate that personality information can be used to create useful proxy measures for applications to cater to a more personalized service (e.g., [8,11,29]).…”
Section: Related Workmentioning
confidence: 99%
“…Personality traits have shown to consist of cues to infer users' behavior, preference, and taste (e.g., [9,26,28]). Hence, knowing one's personality can provide important information for systems to create a personalized user experience.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we focus specifically on personality traits. Personality traits have shown to be an enduring factor with relationships to one's taste, preference, and interest (e.g., [4,15,17]). For example, a finding of Rawlings and Ciancarelli show that extraverts have a preference for pop music [15].…”
Section: Related Workmentioning
confidence: 99%
“…Research has shown that it is possible to infer personality traits from content of social media trails (e.g., Facebook; [1,9,13,16], and Twitter; [8,14], Instagram [5,6]). It has been shown that personality consist of reliable cues to create proxy measures about users' behavior, preference, and taste (e.g., [4,15,17]). However, both methods heavily rely on disclosed content.…”
Section: Introductionmentioning
confidence: 99%